Inovasi Pembelajaran Energi: Operasi PLTU Berbasis Simgenics Operator Training Simulator (OTS) - Tri Vicca Kusumadewi; Ary Bachtiar; Wawan Aries; Maulana Yusuf Izzuddin (Sewagati, 2026)
This community service activity aims to enhance the technical competencies of vocational education students in the field of power generation, particularly in understanding and operating Steam Power Plant (PLTU) systems. The training is designed to be application-oriented by utilizing Simgenics software, an industrial simulator widely used in modern power plant training. Through a simulation- and visualization-based approach, both students and lecturers are expected to gain direct understanding of the main components of a steam power plant, energy flow, as well as operational and control procedures of the generating unit. The training is conducted over 39 hours, consisting of 15 hours of conceptual understanding of power plant materials and 24 hours of operational development through hands-on Simgenics practice. Therefore, this program is expected to serve as a technology-based vocational education development model, strengthen the link and match between academia and industry, and contribute to improving the quality of human resources in the power generation sector.